Challenging Times for Sino–Foreign Sci–Tech Relations - Welch, Anthony (International Higher Education, 2021)
US actions to restrict research collaboration with China in key high-tech science and technology fields is increasingly recognized as part of a tech war, if not an ideological war. Australia, Europe, and Japan, among others, are also instituting measures to limit collaboration in sensitive high-tech areas, citing security concerns and loss of intellectual property. If insufficiently nuanced, such measures pose risks and will potentially weaken well-established and important research networks with China.